2016
DOI: 10.18632/oncotarget.9167
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial GRIM-19 as a potential therapeutic target for STAT3-dependent carcinogenesis of gastric cancer

Abstract: Aberrant STAT3 activation occurs in most human gastric cancers (GCs) and contributes to the malignant progression of GC, but mechanism(s) underlying aberrant STAT3 remain largely unknown. Here we demonstrated that the gene associated with retinoid interferon-induced mortality 19 (GRIM-19) was severely depressed or lost in GC and chronic atrophic gastritis (CAG) tissues and its loss contributed to GC tumorigenesis partly by activating STAT3 signaling. In primary human GC tissues, GRIM-19 was frequently depresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 45 publications
(64 reference statements)
1
33
0
Order By: Relevance
“…FSP is considered as a marker of fibroblasts in different organs undergoing tissue remodeling and helps to identify fibroblasts derived from EMT in several organs including the liver 5859, 60. Herein, we have shown that possible downstream targets of NFκB and STAT3 pathways including TGFβ, HGF, IL‐6, IL‐8, TNC, collagens I and III were upregulated in fibroblasts infected by H. pylori (cagA+vacA+).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…FSP is considered as a marker of fibroblasts in different organs undergoing tissue remodeling and helps to identify fibroblasts derived from EMT in several organs including the liver 5859, 60. Herein, we have shown that possible downstream targets of NFκB and STAT3 pathways including TGFβ, HGF, IL‐6, IL‐8, TNC, collagens I and III were upregulated in fibroblasts infected by H. pylori (cagA+vacA+).…”
Section: Discussionmentioning
confidence: 86%
“…FSP is considered as a marker of fibroblasts in different organs undergoing tissue remodeling and helps to identify fibroblasts derived from EMT in several organs including the liver 58. H. pylori can stimulate TLRs leading to activation of innate immunity against bacterial inflammation, thus creating an inflammatory microenvironment, a prerequisite for tumor development through activation of NF-κB and STAT3 pathways in human GC 59,60. Herein, we have shown that possible downstream targets of NFκB and STAT3 pathways including TGFβ, HGF, IL-6, IL-8, TNC, collagens I and III were upregulated in fibroblasts infected by H. pylori (cagA+vacA+).…”
mentioning
confidence: 99%
“…As STAT3 promotes tumor progression by inducing tumor cell proliferation, inhibiting apoptosis and increasing tumor invasion and metastasis by enhancing EMT, GRIM19‐mediated STAT3 inhibition is also reported to be associated with tumor suppression in many cancers. In brief, GRIM19 expression is decreased and negatively correlates with STAT3 activation in gastric cancer, colon cancer, breast cancer, ovarian cancer, and HCC, leading to poor patient prognosis. As we show that GRIM19 expression is negatively correlated with STAT3 activation, low GRIM19 expression is the significant factor for poor prognosis in patients with HCC.…”
Section: Discussionmentioning
confidence: 99%
“…GRIM-19 is also a component of complex I in the electron transport chain and acts as a chaperone to recruit STAT3 into the inner mitochondrial membrane, thus modulating its mitochondria-specific functions [ 135 ]. Recently, Huang and colleagues suggested mitochondrial GRIM-19 as potential therapeutic target for STAT3-dependent carcinogenesis of gastric cancer [ 73 ].…”
Section: Stat3-interacting Proteinsmentioning
confidence: 99%